Determination of the critical load of eccentrically compressed columns by the second group of limit states - Galagurya Evgeniy; Kovalov Maksym; Kravtsiv Larisa; Bychenok Igor (MATEC Web of Conferences, 2017)
Determination of critical load values of eccentrically loaded columns was subject of studies by such authors as Vatulia G. L., Galagurya E. I., Glazunov Y. V., Zhakin I. A., Opanasenko E. V., Storozhenko L. I., Timoshenko S. P., Trull B. A., Hoff N. D., Chikhladze E. D. and other researchers. However, those works have not studied properly work of statically determinable and statically indeterminable columns, compressed eccentrically at one end and being under the axial compression at the other one. The article deals with the problem of determining the critical load for the following design patterns: a column that is loaded at the ends by longitudinal forces by equal and single-direction eccentricities; a column that is rigidly clamped at the bottom, hinged at the top and loaded by longitudinal force at the upper end eccentrically; column rigidly clamped at the bottom, loaded at the free end of the longitudinal force eccentrically; a hinged column, loaded at the upper end of the longitudinal force eccentrically. Critical load of excentrically loaded columns with different types of bearing and load patterns can be determined using the obtained equations. Allowable deflection value according to the regulatory documents and geometric characteristics of the considered columns should be specified to solve these equations.